The potential contribution of nanotechnology to nutritional well being. - Ramsden, Jeremy J. (Jointly by, Collegium Basilea (Institute of Advanced Study) and Association of Modern Scientific Investigation., 2008)
Hunters and gatherers—our ancestors until about 10 000 years ago—presumably invariably ate fresh food. Given that degradation sets in within seconds of an animal being killed or a fruit or vegetable being plucked, this would appear to be a highly commendable state of affairs, conducive to good health. Nevertheless, hunting and gathering implies that most of man’s waking hours had to be spent in search of food: without leisure, little development of civilization is possible. The cultivation of plants, and the domestication of animals, allowed far greater control of food supply and was far more productive, 1 enabling some time to be set aside for leisure, which itself provided opportunities to develop technology for dealing with the food surpluses that would have accrued at certain times of the year. A variety of familiar preservation technologies—such as butter and cheese, and salt beef and fish—would appear to be very ancient. Other technologies, associated with ploughs (drawn by animals) and irrigation, began to be developed, and other food processing technologies such as making wine and bread emerged (approximately 6000 and 5000 B.C. in Georgia and in Egypt respectively), and agrarian societies, based on large-scale farming, emerged about 5000 years ago. Since then, there has been a continuous expansion of this sector of activity, to the extent that at least in the developed world, probably a majority of food is processed after harvest. The introduction of cold storage by the Vestey brothers and others about a century ago ranks as a major milestone in this development. There is a common thread running through it, namely enhancing productivity allows surpluses to be accumulated, which both enable the leisure that can be used to develop new technology, and require such technology to prevent them from being wasted. Since technology is a collective enterprise, it naturally fosters urbanization, 2 which has been another notable trend ever since the emergence of agrarian societies. The greater the degree of urbanization, the less practicable it is to provide everyone with fresh food, hence processing for the purpose of preserving the comestibility of food becomes more and more necessary. In our present society, this has been extended to include the availability of exotic foods from almost every part of the world, which is nowadays expected as a matter of course even in a small town. 3 Technology is thus inextricably intertwined with the provision of food, and has been for millennia. Now that we stand on the threshold of yet another technological revolution, this time the one associated with nanotechnology, it would appear to be unexceptionable to expect that it will also be exploited by the food industry.
Keywords: agriculture; food production; malnutrition; processing